2003
DOI: 10.1002/yea.1033
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence analysis of the TRP1 gene encoding the phosphoribosyl anthranilate isomerase from Pichia anomala (strain K)

Abstract: Pichia anomala (strain K) is an efficient biocontrol agent against post-harvest diseases affecting apples. To study the role of strain K genes in biocontrol activity, it is useful to identify selectable markers on which to base a gene disruption strategy. The Pichia anomala TRP1 gene (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This includes genes that can complement auxotrophic mutations, such as URA3 (J.A. Perez et al , unpublished: EMBL accession number Y09221), (Ogata et al , 1992), LEU2 (De la Rosa et al , 2001) and TRP1 (Friel et al , 2003), genes involved in the nitrate assimilation (Garcia‐Lugo et al , 2000), an invertase gene (Perez et al , 1996, 2001), SEC61 , which is involved in the secretory pathway (Ruiz et al , 2001, 2003), the gene for the alternative oxidase (Sakajo et al , 1999), and the PaEXG2 gene, encoding an exoglucanase that was suggested to be involved in the antifungal activity of P. anomala (Grevesse et al , 2003).…”
Section: Geneticsmentioning
confidence: 99%
“…This includes genes that can complement auxotrophic mutations, such as URA3 (J.A. Perez et al , unpublished: EMBL accession number Y09221), (Ogata et al , 1992), LEU2 (De la Rosa et al , 2001) and TRP1 (Friel et al , 2003), genes involved in the nitrate assimilation (Garcia‐Lugo et al , 2000), an invertase gene (Perez et al , 1996, 2001), SEC61 , which is involved in the secretory pathway (Ruiz et al , 2001, 2003), the gene for the alternative oxidase (Sakajo et al , 1999), and the PaEXG2 gene, encoding an exoglucanase that was suggested to be involved in the antifungal activity of P. anomala (Grevesse et al , 2003).…”
Section: Geneticsmentioning
confidence: 99%
“…S. fibuligera Trp1 protein shares the highest sequence identity (43.5%) with that of Komagataella pastoris, followed by those of Candida albicans (39.5%), C. orthopsilosis (39.1%), and Wickerhamomyces anomalus (38.4%). The alignment also confirmed several motifs highly conserved among fungal Trp1s: VGVFRNOS at amino acid positions 99-105, DFVQLHG at 120-126, and ILAGGLT at 200-206 (S. fibuligera numbering) [3,8,22]. Analysis by the C-DART program confirmed that S. fibuligera Trp1 shares a conserved structure with the PRAI family [9].…”
mentioning
confidence: 54%
“…Sequence alignment with other Trp1 proteins (Fig. 1) indicated that S. fibuligera Trp1 has a typical primary structure; the previously reported Trp1 domains [8,20] are highly conserved in S. fibuligera Tp1. S. fibuligera Trp1 protein shares the highest sequence identity (43.5%) with that of Komagataella pastoris, followed by those of Candida albicans (39.5%), C. orthopsilosis (39.1%), and Wickerhamomyces anomalus (38.4%).…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…The Saccharomyces cerevisiae strain used was FY1679-18b, MATa ura3-52 leu2D1 trp1D63 his3D200 (Friel et al 2003). Yeasts were transformed using the method LiAc method of Ito et al (1983).…”
Section: Strains Dna Transformation and B-galactosidase Assaysmentioning
confidence: 99%